Investigating the Supply Chain Management of Accessibility Members of Micro and Small Enterprises (MSEs) On Financing Capitals in Aceh Province, Indonesia - Ishak Hasan; Syahril Syahril; Alisman Alisman; Ika Rahmadani; Amsal Irmalis; Jumadil Saputra (International Journal of Supply Chain Management, 2020)
Abstract- The purpose of this study is to investigate the supply chain management effects on accessibility of Micro and Small Enterprises members (MSEs) on capital financing from financial institutions in Aceh province, Indonesia. This cross-sectional data derived from the results of the Economic Census (2016) in Aceh province in 2017 which consists of 23 districts/cities, as many as 34 thousand selected MSEs units. The data analyzed by using logistic-linear regression. The results of this study showed that the status of a business entity, association, business partnership, expert, duration of operation, internet use, membership cooperatives, the provincial minimum wage, and business scale have a significant effect on capital financing Therefore, there four variables do not has a significant on capital financing from financial institutions received by MSEs members namely location, certificate ownership, financial statements and business systems. An astonishing finding is that MSEs members of cooperatives have more than three times the opportunity to receive funding from financial institutions compared to non-MSEs members. It clearly illustrated that MSEs who are members of cooperatives have a substantial possibility of obtaining financing from financial/banking institutions compared to those who are not members of cooperatives. This study suggests that Non-MSEs members to join as MSEs members is a necessity.